2016
DOI: 10.1002/mc.22527
|View full text |Cite
|
Sign up to set email alerts
|

Reelin‐Dab1 signaling system in human colorectal cancer

Abstract: Reelin is an extracellular matrix protein that plays a critical role in neuronal migration. Here we show that the mucosa of human colon expresses reelin, its receptors ApoER2 and VLDLR, and its effector protein Dab1. Immunohistochemical analyses reveal that reelin expression is restricted to pericryptal myofibroblasts; Dab1 is detected at myofibroblasts, the apical domain of surface epithelial and crypt cells, and a strong linear staining is observed at the basement membrane; VLDLR and ApoER2 are in the cytopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 37 publications
4
24
0
Order By: Relevance
“…Opto-Dab1 may also be useful to study Reelin-Dab1 signaling in synaptic plasticity140, in the development of non-neuronal tissues, such as mammary gland, small intestine and limbs, and in diseases including cancer414243. These applications will require the development of techniques to express opto-Dab1 effectively in the target cell types and to direct light to the respective tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Opto-Dab1 may also be useful to study Reelin-Dab1 signaling in synaptic plasticity140, in the development of non-neuronal tissues, such as mammary gland, small intestine and limbs, and in diseases including cancer414243. These applications will require the development of techniques to express opto-Dab1 effectively in the target cell types and to direct light to the respective tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies discovered RELN in peripheral organ systems as well. It has been found inter alia in human blood, liver, pancreas, mamma and intestines [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Alterations in RELN function are associated with several medical conditions in human beings. Amongst these are neuropsychiatric disorders such as schizophrenia, lissencephaly and Alzheimer's disease as well as a variety of other diseases, for instance cancerous diseases [24][25][26]. In schizophrenia for example, epigenetic changes lead to downregulation of cerebral RELN expression, while a mutation in the RELN gene is responsible for an autosomal recessive form of lissencephaly [27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…The earliest direct evidence was based on the postmortem studies of patients with SCZ, which revealed that RELN mRNA was reduced up to 50% in several regions of the brain [ 19 , 20 ]. Additionally, RELN had been shown to be expressed in organ systems, inter alia in human blood, liver, pancreas, breast and intestines [ 21 26 ]. A recent study determined that the patients with SCZ had higher level of RELN gene methylation compared to healthy controls, leading to a subsequent 25-fold decrease in RELN expression in the methylated group [ 27 ].…”
Section: Introductionmentioning
confidence: 99%